Pengaruh Gliserin dan Asam Asetat pada Pembuatan Bioplastik dari Tepung Tapioka dan Maizena - Nurfatihayati Nurfatihayati; Cory Dian Alfarisi; Drastinawati Drastinawati; Aldo Seveno Mahendra (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2023)
Bioplastics are destructive plastics that break down by the environment, humidity, and microorganism activity. Bioplastics can be used just like conventional plaques. Bioplastics include natural polymers made from plant and animal materials. Tapioca flour is pure starch obtained from the extraction of cassava milling and continues to amylose and amylopectin. Maize flour is flour obtained by grinding clean and good corn kernels through the process of obtaining skin, endosperms, institutions, and the tip of the hat. This research helps make bioplastics using tapioca flour as an adhesive and cornstarch as an efficient thickener. The use of tapioca flour and cornstarch in producing bioplastics was using the blending method. Variations in the amount of acetic acid were 2 ml, 4 ml, and 6 ml, the amount of glycerin was 2 ml, 4 ml, and 6 ml, and tapioca flour and cornstarch were 6 gr at 700oC. Bioplastics are made by mixing 6 gr tapioca flour and 6 gr cornstarch, 50 ml distilled water, and heated to a temperature of 700oC. Bioplastic test results announced by the fourth bioplastic (2.649 MPa), the best thickness possessed by the ninth bioplastic (0.12 mm), the best resistance needed by the eighth bioplastic (46.15%), and the fastest or best degradation time by bioplastics three and ninth (6 days). The effect of using glycerin is very dominant in the test results but not for the use of acetic acid.